MIS Practices in Banking Sector: A Case Study on Prime Bank Limited - Miah, Md. Rahimullah; Kar, Nomita (Asian Accounting and Auditing Advancement, 2017)
An explorative field study to determine the MIS Practices in Banking Sectors in the Sylhet urban area was conducted at the Prime Bank Limited at Subidbazar Branch in Sylhet over the period of three months for providing information to support operations, management & decision-making functions. It is one of the important systems for Prime Bank Limited to achieve organizational goals and Information Systems play a role in the competitive structure of an organization. It attempts to evaluate the development of this branch in terms of MIS application and find out the major problems and prospects in this area by using different types of methods. This reflects MIS’s potential to produce high economic profit and perceived demographic trends toward an expanded business. The field study details the principles recognizing the results carefully with achievements mentioned the existing status of management information systems in Sylhet urban banking to stare as a study in regional matter. The phenomena of effective MIS were identified based on a literature review and interviews with customers, account holders, and pertinent respondents. This research highlights the aspects of the impact of MIS with the online integrated banking approaches and the learning strategies of these in urban Banks. The study also focused on the concept and overview of coordination, collaboration, and social networking and gave steps required for network banking awareness of the mentioned Banks in the city. Prime Bank Limited is concerned about the practices of Information Technology as MIS is used for planning, controlling, and monitoring at the management level. Overall, it was concluded that MIS practices in the Prime Bank Limited need some network extension for growth and development. It is obvious that the improvement activities create the base for Prime Bank Limited in the zone. But there is some significant lacking in terms of MIS. Finally, we focus on future research trajectories of the executive approaches and recommendations for how to further improve the MIS practices in Prime Bank for the present and upcoming generations as it is a long-term perspective and continuous process.